Banking and Finance: Islamic Concept Edited by Mukhtar Zaman. Karachi: International Association of Islamic Banks, 1993, 204 pp. (American Journal of Islam and Society, 1994)
This book features a selection of articles dealing with interest (riba)and other related issues and is mainly an appraisal of the interest-freesystem as an alternative to the western fixed-rate system. Seven essaysdeal with the experience of Islamic banking in Pakistan. Ziauddin Ahmedand Nawazish A. Zaidi highlight some of the concerns associated withimplementing Islamic banking practices. Although these cancems atequite real, the appmh is more anecQtal than empirical. nK essays ofGhulam Khan, D. M. Qureshi, and Tariq Hassan, as well as the StateBank of Pakistan's article on Islamic modes of financing, provide prudentdescriptions of how Islamic financial instnunen ts have been implementedin Pakistan. They also discuss various problems, a common one beingthat most (if not all) Islamic countries ate developing countries and,therefore, the transition to Islamic banking is inseparable from the mdimentarynature of their present banking systems.Jalees A. Faruqui's article analyzes some of the ideologicaldiffemces between the Islamic, capitalist, and socialist ecoflofILic systems.The capitalist system is Qminated by individualism and selfintetest,whems a staple element of the socialist system is the conceptof class warfare. The Islamic system differs from the other two in oneimportant way: it gives people individual rights, but in the context ofcaring for others. 'This characteristic means that an equitable distributionof h m e is an inherent, rather than an institutionalized, part of thesystem The final article in this section, by Haqqani, makes the point thata mudarbah certificak is nothing but a share certificate ...